2005
DOI: 10.1111/j.1439-0426.2005.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

To be, or not to be, a non-native freshwater fish?

Abstract: We examine the evolving concept of what constitutes a nonnative (or alien) freshwater fish. In an attempt to distinguish between biogeographical and socio-political perspectives, we review the patterns in the introduction and dispersal of nonnative fishes in Europe and North America, and especially the recent expansion of Ponto-Caspian gobies in Europe. We assess patterns in the development of national policy and legislation in response to the perceived threat of non-native fish introductions to native species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
512
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(522 citation statements)
references
References 72 publications
4
512
2
4
Order By: Relevance
“…P. glenii threat the native ichthyofauna by competition, displacement, and direct predation (Bogutskaya and Naseka 2002, Koščo et al 2003, Witkowski 2003, Reshetnikov 2003, 2004, Kostrzewa et al 2004, Copp et al 2005. Furthermore, it has been demonstrated that this species may be a vector of certain parasites and fungi (Czeczuga et al 2002, Koščo et al 2003, Uzunova and Zlatanova 2007.…”
Section: Fig 1 Occurrence Of the Perccottus Glenii In Polandmentioning
confidence: 99%
“…P. glenii threat the native ichthyofauna by competition, displacement, and direct predation (Bogutskaya and Naseka 2002, Koščo et al 2003, Witkowski 2003, Reshetnikov 2003, 2004, Kostrzewa et al 2004, Copp et al 2005. Furthermore, it has been demonstrated that this species may be a vector of certain parasites and fungi (Czeczuga et al 2002, Koščo et al 2003, Uzunova and Zlatanova 2007.…”
Section: Fig 1 Occurrence Of the Perccottus Glenii In Polandmentioning
confidence: 99%
“…So far, six gobiid species have been recorded in Europe as non-native species, including bighead goby Ponticola kessleri, Caspian bighead goby P. gorlap, monkey goby Neogobius fluviatilis, racer goby Babka gymnotrachelus, round goby N. melanostomus and Western tubenose goby Proterorhinus semilunaris. These species have invaded or expanded their range in large European rivers such as the Danube (Ahnelt et al 1998(Ahnelt et al , 2001Kautman 2001;Naseka et al 2005), Rhine (Freyhof 2003;van Kessel et al 2009), Vistula (Grabowska et al 2008) and Volga (Copp et al 2005). The Ponto-Caspian gobies are relatively small (up to 15-20 cm total length), bottom-dwelling species that are usually associated with crevice habitats, though some invading populations have been reported to have established in sandy areas (Sapota 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the most impressive fish invasions in European inland waters in recent decades are those of the topmouth gudgeon Pseudorasbora parva, which occurred mainly as a contaminant of fish transport (see Copp et al 2005;Simon et al 2011), and of the Ponto-Caspian gobies, which colonized new areas mainly by natural dispersal via inter-basin connections, e.g. being transported by river ships (see Grabowska 2005 andWiesner 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The black-stripped pipefish is now widely distributed and abundant in all the Dnieper dam reservoirs (Romanenko et al 2003). The bighead goby also has a large invasive potential, considering its invasive history and fast spread in the Ukrainian part of the Dnieper River as well as in the Danube system (Copp et al 2005). The other Ponto-Caspian fish-the stellate tadpole goby-entered the Kiev Reservoir immediately after its construction in the 1980s and recently was found in the reservoir's upstream section (Zimbalevskaya et al 1989, Romanenko et al 2003.…”
mentioning
confidence: 99%